The white racial frame of public health discourses about racialized health differences and "disparities": what it reveals about power and how it thwarts health equity - Lisa Bowleg; Lisa Bowleg (Frontiers Media S.A., 2023)
Although several public health scholars have advocated for more clarity about concepts such as health disparities and health equity, attention to the framing of public health discourses about racialized health differences and "disparities" in the U.S., and what it reveals about power and the potential for achieving health equity, is surprisingly rare. Sociologist Joe Feagin, in his book, The White Racial Frame: Centuries of Racial Framing and Counter-Framing coined the term white racial frame to describe the predominantly white racialized worldview of majority white and white-oriented decisionmakers in everyday and institutional operations. Informed by insights from critical race theories about the white racial frame, white epistemological ignorance, and colorblind racism; critical perspectives on social class; Black feminist perspectives; framing; and critical discourse analysis, in this perspective I discuss: (1) the power of language and discourses; (2) the white racial frame of three common public health discourses - health disparities, "race," and social determinants of health (SDOH); (3) the costs and consequences of the white racial frame for advancing health equity; and (4) the need for more counter and critical theoretical frames to inform discourses, and in turn research and political advocacy to advance health equity in the U.S.